Історія приміських трамвайних ліній Києва. IV. Дарницький (Слобідський) трамвай - Машкевич, С. (Краєзнавство, 2017)
Стаття присвячена історії Дарницького (Слобiдського) трамвая — першої трамвайної лінії в
Києві, яка перетнула Дніпро. Ця лінія працювала з 1912 по 1941 рік, спочатку як приватне підприємство,
потім як частина загальноміської трамвайної системи. The subject of the article is the history of the Darnytsya (Slobidka) tram, the first tram line in Kiev to have
crossed the Dnieper. The idea of building a trans-Dnieper tram link dates back to the late XIX century, but was
only implemented in the early 1910s, through an effort by the engineer Valery Timchenko, who was also the main
stockholder of the private enterprise which owned the line. Service started in 1912. Initially, it was not electrified,
using gasoline-powered cars (so-called «mototrams») instead. The main line ran from Kyiv to the town of Brovary,
with a branch to the Darnytsya railway station. A vital rail link connecting left-bank workers’ settlements with
Kyiv and offering passenger service at an affordable price, it quickly gained considerable popularity.
Service was interrupted in 1920 when the Niholas Chain Bridge was blown up by Polish troops, and resumed
in 1925 when the new Yevgenia Bosch bridge was completed. The pre-revolutionary network was quickly
reinstated. By 1934, it was fully electrified. In 1936, an extension to the settlement of DVRZ was added, which
is the only fragment of the four former Kyiv suburban lines still in service today. The Darnytsya network as a
whole ceased to exist in 1941, when the Soviet troops’ blew up the Yevgenia Bosch bridge. Статья посвящена истории Дарницкого (Слободского) трамвая — первой трамвайной линии в
Киеве, которая пересекла Днепр. Эта линия работала с 1912 по 1941 год, сначала как частное предприятие, затем как часть общегородской трамвайной системы.